The Origin and Meaning of Social Openness in Bergson’s and Popper’s Thought - Aleksandravičius, Povilas (Problemos, 2019)
[full article and abstract in Lithuanian; abstract in English] The article is focused on the analysis of the origin and meaning of social openness in Henri Bergson’s and Karl Popper’s thinking. It aims to reveal the foundational significance of the concept of open society in the works of its creators. The first part of the article is focused on Bergson’s research into formation of closed society, the vantage point being the analysis of a human being’s reaction to death. The second part reveals H. Bergson’s process of social openness; its anthropological foundation is the conversion of instinct into intuition or the contact with the principle of élan vital, realized by the mind. The third part analyses Popper’s concept of closed and open society in the context of Bergson’s philosophy.